Human adult odontometrics the study of variation in adult tooth size - Kieser, Julius A. (Cambridge studies in biological and evolutionary anthropology, 1990)
An appreciation of the genetic and environmental determinants of tooth size is fundamental to an understanding of the metric variation of teeth in humans. Thus, besides imparting a sound knowledge of the theories of dental inheritance, development and evolution, this book has an important role in demonstrating the diverse practical applications of odontometrics. A particular feature of the book is the inclusion of numerous tables which bring together a vast body of information on tooth size in different population groups. Students of oral biology, orthodontics, physical anthropology, human biology, forensic science and archaeology will find this work of great value as a text and reference source. As Professor Phillip Tobias writes in the foreword, 'The breadth of Dr Kieser's reading, and his mastery of a staggering array of anthropological, evolutionary, embryological, orthodontic and statistical concepts shine through every page of this work'